Simulations of Dedicated LEO-PNT Systems for Precise Point Positioning : Methodology, Parameter Analysis, and Accuracy Evaluation - Prol, Fabricio S.; Bhuiyan, M. Zahidul H.; Kaasalainen, Sanna; Lohan, E. Simona; Praks, Jaan; Çelikbilek, Kaan; Kuusniemi, Heidi (IEEE, 2024)
Low earth orbit (LEO) satellites provide the potential to overcome the current limitations in global navigation satellite systems (GNSSs) due to the increased satellite velocity and signal reception power. As the whole LEO segment grows, preliminary studies and simulations have been conducted in the most recent years to identify how to develop a LEO positioning, navigation, and timing (PNT) system and add value to the GNSS. To promote the development of LEO-PNT, this work presents the simulation of several key components of a dedicated LEO-PNT system. Our investigation analyzes features of the satellite constellation, orbits, onboard instruments, signal propagation effects, and user measurements and maps the accuracy of the service on the ground. The analysis considers the signal propagation from both LEO and medium earth orbit satellites and provides the expected accuracy of a ground user when certain system parameters and instruments are defined in the space mission design. All parameters and statistical distributions, which can serve to future LEO-PNT simulations and developments, are presented. For validation and demonstration, a comparison is presented to analyze the expected positioning errors for LEO satellites and how they differ from the classic GNSS. Our investigation enables a valuable quantitative analysis of the dedicated LEO-PNT systems and provides analysis for LEO-PNT system design optimization.
Keywords: Clock; global navigation satellite system (GNSS); low earth orbit (LEO); positioning; precise orbit determination (POD); simulation; navigation; fi=Tietotekniikka|en=Computer Science|